Contribution of farmers’ network to income poverty reduction: A case of Ludewa district - Lupembe, Gervas Alfred (Mzumbe University, 2024)
A dissertation submitted to Institute of Development Studies in partial fulfillment of the requirements for award of the Degree of Master of Science in Development Policy (Msc. DP) of Mzumbe University